Unpacking the Resilience-Performance Nexus in African MSMEs: A Systematic Literature Review - Tete, Felix; Chikoko, Laurine; Mutongoreni , Noah Ariel (Philippine Social Science Journal, 2025)
This systematic review examines the crucial link between resilience and performance in African Micro, Small, and Medium Enterprises (MSMEs). By analyzing existing literature, the study identifies key factors driving MSME resilience and their impact on business performance. Findings highlight that adaptive capacity, sound financial management, market responsiveness, and strong networks are essential for enhancing both resilience and performance. These insights underscore the need for targeted support systems to bolster MSME sustainability and competitiveness, offering valuable guidance to policymakers, practitioners, and researchers working towards fostering sustainable economic development across Africa.